(untitled) (Medical Forum Monthly, 2023)
Objective: To assess barriers in obtaining dating scan by women of reproductive age of Lahore. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Central Park Teaching Hospital from April 2021 to October 2021. Methods: A detailed sociodemographic history and parameters were recorded including age, education and socioeconomic status. Obstacles in getting dating scan were assessed using a 9-item questionnaire which records responses in terms of yes and no. Data was imported to SPSS version 26.0 from Microsoft excel for statistical analysis. Data was stratified based on socioeconomic status, level of education and age. The study parameters were compared and correlated by using chi-square comparison and correlation test. For significance, a cutoff of p value of 0.05 was set as standard. Results: The mean age for study participants (n=400) was noted as 32.09 + 6.94 year with age range of 18 to 45 years of age. 51.25% of women belonged to lower socioeconomic status while 49.75% had higher socioeconomic status. 25.75% (n=103) were illiterate, 36% (n=144) were matric and below and 38.25% (n=153) were those who had education above matric till masters. older women were reluctant to visit healthcare facilities when compared to younger females (21.20% v/s 5.22%) with the p value of 0.0001. Low income was a major obstacle in obtaining dating scan as compared to high income (47.26% v/s 9.55%) with p value of 0.0001. More the education greater the knowledge of antenatal care was observed between study groups as with p value of 0.0001. Conclusion: Lack of knowledge regarding dating scan, poor socioeconomic status, age more than 35 years, un cooperative attitude of husband and family members are the major obstacles in obtaining dating scan.